Determination of average lengths of concentration waves and of the diffusion coefficient of the critical n-amylic alcohol-nitromethane mixture - Mikołaj ŁABOWSKI; Tomasz HORNOWSKI (Archives of Acoustics)
The kinetics of concentration fluctuations in the critical n-amylic alcohol-nitromethane mixture have been analysed in this paper. Average lengths of concentration waves and the diffusion coefficient for investigated mixtures have been established on the basis of results obtained previously by the authors from estimations of the average relaxation time of concentration fluctuations and the radius of their correlation.